Effects of Rearing Structure on The Growth and Survival of Pearl Oysters (Pinctada maxima) - Windi Juli Ani; Muhammad Junaidi; Zaenal Abidin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
West Nusa Tenggara (NTB) is one of the provinces that cultivates many Pinctada maxima pearl oysters. Seed dispersal is a stage that can influence the growth and activity of pearl oysters because they will be moved from the hatchery to the sea. The use of appropriate containers in pearl oyster seed dispersal very necessary to prevent pearl oysters from being carried away by currents or attaching biofouling as a nuisance to biota. The aim of this research is to determine the effect of rearing containers on the growth and survival of pearl oysters (Pinctada maxima). This research used an experimental method using a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used are different types of keeping containers, namely using traditional containers, pocket baskets, waring baskets and lantern baskets. The results of the research showed that rearing pearl oyster spat (Pinctada maxima) for 60 days in Ekas Bay with the influence of different containers showed that the average absolute length growth obtained was 1.80-3.88 cm, the absolute weight ranged from 12.3 -31.10 g and survival rate 38.86 – 83.30%. The conclusion from this research is that using pocket baskets is better than other containers.